(untitled) (Al-Academy, 2016)
Evolution in the modern era Which led to the rapid change in the forms of industrial products For many reasons, So put current research into question the view (What are the design requirements that define the formal change in the Iron clothes)? To reach the aim of In the design cornerstonesUnderlying the formal changethe Iron of the clothes, In the first section shed light on the development stages of systems design lists the historic stages of development and energy operator devices irons and mechanism of action and internal components, while in the second part, which was entitled (The role of technology and the factors influencing the change formality of Iron) touched on the three topics which technology modern industrial and receiver, as well as technological development and formal change and last topic is the role of the designer in the user accepts the morphological changes of industrial products, and research found that formal change subject effectively on the evolution in the field of technology